Efficacy and safety of incobotulinum toxin A in periocular rhytides and masseteric hypertrophy: side-by-side comparison with onabotulinum toxin A. (August 2013) - Lee, Jae Hyung; Park, Ji Ho; Lee, Soo Keun; Han, Kwang Ho; Kim, Sang Duck; Yoon, Chun Sik; Park, Jae Young; Lee, Joo Heung; Yang, Jun Mo; Lee, Jong Hee
Background: Incobotulinum is a newly developed botulinum toxin A in which the complexing proteins had been removed. Objective: The aim was to compare the efficacy and safety of incobotulinum with onabotulinum in treating periocular rhytides and masseteric hypertrophy. Methods: A randomized, double-blind, split-face study was planned. Fifty-six patients were treated for periocular rhytides and the other 56 patients were treated for masseteric hypertrophy. Onabotulinum was injected on one side of the face and incobotulinum was injected on the other side of the face. The degree of periocular rhytides and masseteric hypertrophy was rated using Fitzpatrick Wrinkle Classification System (FWCS) and 10-point visual analogue scale (VAS) (0: the minimum to 10: the maximum). Objective and subjective rating was performed at pretreatment and every posttreatment follow-up visit by investigators and subjects. Result: The efficacy and safety of incobotulinum were not inferior to those of onabotulinum in treating periocular rhytides and masseteric hypertrophy up to 16 weeks after injection. There were no noteworthy differences in the onset time of effect between two botulinum toxins for periocular wrinkles and masseteric hypertrophy. No adverse event was reported. Conclusion: Incobotulinum provided non-inferior efficacy and safety for the treatment of periocular rhytides and masseteric hypertrophy compared with classic onabotulinum.